THE CONTROL ORGANS OF THE PUBLIC ADMINISTRATION OF THE PROVINCE OF LA PAMPA AND ITS CONTRAST WITH OTHER CONTROL SYSTEMS (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
Public control emerges as the very structure of state power, and it imposes itself as a regulator of the public acts. It corresponds that the public works be watched over so that it responds to the very own purposes of the state, within a regime of freedoms and in agreement with the competences that are assigned to it. Together with this public control comes responsibility for those who practice authority. These two actors, require the adoption of tools and methods so as to verify the correct fulfillment of the normative, expenses and inversion of the public treasure.In this way it is observed that in different jurisdictions al least four expressions of control are used: previous, preventive, and posterior control. These are introduced as bodies that would or would not practice it independently of the public organization that is being controlled. As for the integrality of the control in terms of place and moment, may generate multiple possible solutions.The aim of the present work is to compare the outstanding solutions. During the 1990 decade in our country there were some significant changes as regards the control systems. We will now make a description of the intern and extern control in our nation and in some of our provinces of our country.
Keywords: Control; audit; responsability; concomitance